2011
DOI: 10.1016/j.ejps.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gastrointestinal pH, fluid and lymphoid tissue in the guinea pig, rabbit and pig, and implications for their use in drug development

Abstract: Laboratory animals are often used in drug delivery and research. However, basic information about their gastrointestinal pH, fluid volume, and lymphoid tissue is not completely known. We have investigated these in, post-mortem, healthy guinea pigs, rabbits, and the pigs to assess their suitability for pre-clinical studies by comparing the results with reported human literature. The mean gastric pH (fed ad libitum) was 3.1 and 4.4 in guinea pig and pig respectively. In contrast, a very low pH (1.5) was recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 22 publications
7
115
1
Order By: Relevance
“…These results indicated that the recombinant ZHD101 produced by L. reuteri pNZ-zhd101 is in an active form at pH 7.0. The mean pH values in small intestine, caecum, and colon of swine are 6.5, 6.1, and 6.5, respectively [28], while the mean pH values in crop, small intestine, caecum, and colon of chickens are 6.1, 6.4, 6.4, and 6.6, respectively [29]. Since the intestinal environments are mildly acidic to neutral, we believe that the recombinant ZHD101 produced by L. reuteri pNZ-zhd101 can be directly delivered to the intestinal tract in an active form.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the recombinant ZHD101 produced by L. reuteri pNZ-zhd101 is in an active form at pH 7.0. The mean pH values in small intestine, caecum, and colon of swine are 6.5, 6.1, and 6.5, respectively [28], while the mean pH values in crop, small intestine, caecum, and colon of chickens are 6.1, 6.4, 6.4, and 6.6, respectively [29]. Since the intestinal environments are mildly acidic to neutral, we believe that the recombinant ZHD101 produced by L. reuteri pNZ-zhd101 can be directly delivered to the intestinal tract in an active form.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiological traits of their GI tracts differ. Merchant et al (2011) reported that pigs have a longer gut (∼24 m; 2.4 cm/kg body weight) compared with humans (8.9 m; 14 cm/kg body weight). This difference in gut length affects the time taken by ingesta, such as food/feed including probiotics, to pass through the GIT; hence, in our model, we modified the incubation time to simulate the pig intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The pig GIT simulation model was based on the human model (Oomen et al 2003) with modifications to the mucin concentration, pH, and incubation time, to optimize it more closely to the physiological traits of pigs (Kararli 1995; Merchant et al 2011). The modified factors and the constituents and concentrations of the various synthetic juices are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Before reaching the distal part of the intestinal (Peng et al, 2014). The mean pH (fed ad libitum) values of the porcine stomach and small intestine are 4.4 and 6.1-6.7, respectively (Merchant et al, 2011). Therefore, the At-Bgl should have high potential for use as catalysts in animal feeds.…”
Section: Optimal Ph and Temperature And Stabilitymentioning
confidence: 99%